2015
DOI: 10.4143/crt.2014.180
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Change in Pre-radiation Therapy Computed Tomography Is a Risk Factor for Severe Radiation Pneumonitis

Abstract: PurposeWe examined clinical and dosimetric factors as predictors of symptomatic radiation pneumonitis (RP) in lung cancer patients and evaluated the relationship between interstitial lung changes in the pre-radiotherapy (RT) computed tomography (CT) and symptomatic RP.Materials and MethodsMedical records and dose volume histogram data of 60 lung cancer patients from August 2005 to July 2006 were analyzed. All patients were treated with three dimensional (3D) conformal RT of median 56.9 Gy. We assessed the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
4
48
1
1
Order By: Relevance
“…The risk factors for radiation pneumonitis have been reported to include the timing and schedule of RT sessions, the mean lung dose, the target volume and dose, pre-existing lung disease, and circulating cytokines. [22][23][24] The risk factors for immunotherapy-related pneumonitis have not been defined; however, suggestions have included active smoking, which we were unable to confirm in our study. 25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival.…”
Section: Discussionmentioning
confidence: 64%
“…The risk factors for radiation pneumonitis have been reported to include the timing and schedule of RT sessions, the mean lung dose, the target volume and dose, pre-existing lung disease, and circulating cytokines. [22][23][24] The risk factors for immunotherapy-related pneumonitis have not been defined; however, suggestions have included active smoking, which we were unable to confirm in our study. 25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival.…”
Section: Discussionmentioning
confidence: 64%
“…Radiation pneumonitis is one of the most critical pulmonary toxicities following SBRT for lung tumors. Many previous radiation pneumonitis studies have investigated risk factors (12,(28)(29)(30)(31), dose-volumetric analyses (32,33), and prophylactic drugs (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…IIPs are one risk factor for the development of radiation pneumonitis (30,31). Several reports have suggested that radiation pneumonitis ≥ grade 3 in patients with IIPs may have certain etiological features in common with acute exacerbations of IIPs (7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that the interstitial changes in the pre-RT chest CT scan (p ¼ .009), mean lung dose (p < .001), and the percentage of lung volume receiving over 30 Gy (V30) (p < .001) significantly predicted RP on multivariate analysis. Therefore, despite the comparatively small field and minimal irradiation volume of SBRT, clinicians should consider the possibility of exacerbated IP [25].…”
Section: Grade 5 Pfmentioning
confidence: 99%